1996
DOI: 10.1111/j.1365-3148.1996.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of prostaglandin E1 during preparation of platelet concentrates

Abstract: A paired study in 10 autologous volunteer donors was undertaken to investigate the efficacy of adding prostaglandin E1 (PGE1) in vitro during routine platelet concentrate (PC) production. After 5 days storage, PCs prepared with PGE1 were compared with control PCs. In vivo platelet recovery, survival and biodistribution were determined following autologous infusion of indium-111 labelled platelets into volunteers, together with the in vitro evaluation of platelet function and biochemistry. PGE1 facilitated easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…The results suggested less PLT aggregate formation during storage as well as easier and faster PLT resuspension after centrifugation. However, due to the measured reduction in in vivo survival in this study, this concept was not further pursued in routine production . If visible aggregates are present after the collection, it could be beneficial to rest the PLTs at least for 1 h without agitation, with the bag label‐side down followed by subsequent agitation for at least another hour (likewise with the bag label‐side down).…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested less PLT aggregate formation during storage as well as easier and faster PLT resuspension after centrifugation. However, due to the measured reduction in in vivo survival in this study, this concept was not further pursued in routine production . If visible aggregates are present after the collection, it could be beneficial to rest the PLTs at least for 1 h without agitation, with the bag label‐side down followed by subsequent agitation for at least another hour (likewise with the bag label‐side down).…”
Section: Resultsmentioning
confidence: 99%
“…To treat hemostatic abnormalities caused by thrombocytopenia, thrombocytopathy, or both, platelets in PGE 1 ‐treated PC should act normally after transfusion. The inhibitory effect of PGE 1 on platelets is considered to be reversible, but it was necessary to confirm the reversibility in vitro before a PGE 1 ‐treated PC transfusion is performed. In this study, the collagen‐ or ADP‐induced platelet aggregation was clearly inhibited by PGE 1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to resuspend platelet pellets following the high‐speed centrifugation caused by platelet activation. Platelet activation during PC preparation contributes to the development of platelet storage lesions and decreased platelet viability . It is therefore important to develop a method to minimize platelet activation during the preparation of PC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E1 (PGE1) inhibits platelet aggregation during storage that is reversed when the platelets are resuspended in a PGE1 free media . However, earlier studies found reduced in vivo survival of PGE1 treated platelets after 5 days of storage, and note that the inhibitory effects of PGE1 are lost after 5 days of storage . Other reversible inhibitors of platelet activation have been investigated, including GPIIb‐IIIa blockade, a polyphenol derived from green tea, nitric oxide, and the phosphodiesterase inhibitor theophylline …”
Section: Liquid Stored Plateletsmentioning
confidence: 99%